Prevalence of Thyroid Disorders among Pregnant and Non-Pregnant Women Attending a Tertiary Care Center in Kathmandu - Pokhrel, Asmita; Pokhrel, Buddhi Raj; Bhattarai, Richa; Khanal, Madhav; Neupane, Nayan; Thakali, Anu; Shrestha, Astha (Nepal Medical College Journal, 2024)
Thyroid hormones are crucial for the overall development of the fetus, and their impact on the pregnancy outcomes needs to be considered seriously. Hence, universal screening for thyroid disorders is recommended in the first trimester of pregnancy. One hundred pregnant women in their first trimester and 100 non-pregnant women of the reproductive age group were screened for thyroid function test. The prevalence of thyroid disorders among the total participants was 32.0% of which 23.5% were hypothyroid and 8.5% were hyperthyroid. Pregnant females had a significantly higher prevalence of thyroid disorders (46.0%) than non-pregnant counterparts (18.0%; P <0.001). Pregnant females had significantly higher odds of hypothyroid disorders than non-pregnant females (OR 3.95; P <0.001). The prevalence of subclinical hypothyroidism among pregnant and non-pregnant was 34.0% and 12.0% respectively which makes it the most common thyroid disorder in both study groups. The median values of FT3, FT4, and TSH levels were, however, not significantly different between the study groups. After adjusting for the confounding effect of age, the odds of thyroid disorders were still significantly higher in pregnant women than in non-pregnant (p =0.001). The prevalence of thyroid disorders, specifically hypothyroidism, is higher in pregnant women compared to non-pregnant counterparts. And this emphasizes on the need of antenatal thyroid screening to be made mandatory in the health policy.